Analisis Faktor Faktor yang Mempengaruhi Indeks Pembangunan Manusia di Provinsi Kalimantan Barat - Asura, Miftah; Putri, Aulia Kusuma; Tampubolon, Era Evalin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to identify the factors that influence the Human Development Index (HDI) in the province of West Kalimantan. The variables analyzed in this study include Gross Regional Domestic Product (GRDP), the Percentage of Poor Population (PPP), the Open Unemployment Rate (OUR), and the Average Length of Schooling (ALS). The data used in this study covers observations from 2019 to 2023, with a total of 75 districts/cities in West Kalimantan. Through multiple linear regression analysis, this study found that GRDP and ALS have a significant impact on HDI, while PPP and OUR show a negative relationship with HDI, although OUR has a significant influence. The regression model developed explains about 88.59% of the variation in HDI in this province, indicating that economic and social variables play a significant role in improving the quality of life. This study also conducted classical assumption tests, including linearity, homoscedasticity, and residual normality, all of which show that the regression model used meets the basic assumptions. The findings of this study are expected to provide insights for policymakers in designing more effective development strategies to improve HDI in West Kalimantan.